Infliximab in hidradenitis suppurativa: A systematic review and meta‐analysis. Issue 9 (18th July 2022) - Shih, Terri; Lee, Katrina; Grogan, Tristan; De, Devea R.; Shi, Vivian Y.; Hsiao, Jennifer L.
Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory often recalcitrant to treatment. There is a lack of an updated systematic data review for infliximab use in HS. We conducted a systematic review and meta‐analysis of literature on infliximab in HS. This study was performed following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines and was pre‐registered on PROSPERO (CRD42021283596). In 9/2021, MEDLINE and EMBASE were systematically searched for articles on infliximab in HS. Non‐English, duplicate, and studies with <5 HS patients were excluded. Study quality was assessed utilizing Cochrane Risk of Bias for prospective trials and Newcastle‐Ottawa Scale for cohort studies . Random effects meta‐analytical model, Cochran's Q statistic, and I squared index were performed. Nineteen articles (314 patients) met inclusion criteria (six prospective, 13 retrospective studies). All patients with HS severity data available ( n = 299) had moderate‐to‐severe disease. Outcome measures used for meta‐analysis of the pooled response rate were largely based on clinician reported outcomes (16 studies). One utilized both clinician and patient assessment. Two utilized patient‐reported response alone. The pooled response rate of HS patients to infliximab was 83% (95% CI, 0.71–0.91). The most common adverse events (AEs) included non‐serious infections (13.2%) and infusion reaction (2.9%). The rate of serious AEs was 2.9%. Study limitations include the small number of prospective studies and heterogeneity between studies. Overall, infliximab is an effective treatment for moderate‐to‐severe HS. Efficacy of infliximab in HS should be compared to other biologics in larger, randomized controlled trials.